How About Good Corporate Governance, How About Good Corporate Governance, Size, Leverage, Financial Performance - Mujiyati Mujiyati; Ovi Itsnaini Ulynnuha (Universitas Muhammadiyah Surakarta, 2023)
This study aimed to find empirical evidence that the board of commissioners, the board of directors, the audit committee, independent commissioners, institutional ownership, leverage, and firm size affect the performance of the company,. financial performance of companies listed on the Jakarta Islamic Index (JII). The population of this study included companies registered in the Jakarta Islamic Index (JII) from 2019 to 2021. Sampling was carried out by purposeful sampling method, based on criteria established, a sample of 20 companies was obtained. Data analysis techniques use classical hypothesis testing, namely normality test, multicollinearity test, variable variance test and autocorrelation test. Hypothesis testing by multiple regression analysis. Research results show that board of directors, board of directors, institutional ownership, firm size and audit committee have no influence on financial performance. Meanwhile, independent trustees and leverage have a positive effect on financial performance.